Amylosporus sulcatus sp. nov. (Russulales, Basidiomycota) from Southern China. Issue 4 (2nd October 2018) - Huang, Fu-Chang; Liu, Bin; Wu, Hao; Qin, Pei-Sheng; Li, Jin-Feng
Abstract: Amylosporus sulcatus sp. nov. is described from Nonggang Nature Reserve, southern China, on the basis of morphological and molecular data. The morphological description and illustrations for the new species are provided. The species is characterized by pileate and stipitate basidiocarps. The pileus surface is obviously concentrically and radiately sulcate and tomentum, and the pore surface is snow white. Phylogenetic analyses based on sequences of the internal transcribed spacer and nuclear large subunit ribosomal DNA confirmed it to be a new species.